100 years of ecology: what are our concepts and are they useful - Reiners, William A.; Lockwood, Jeffrey A.; Reiners, Derek S.; Prager, Steven D. (Wiley, 2017)
On the occasion of the Ecological Society of America's centennial, we sought to learn which ecological concepts members value in terms of their utility. This required defining “concept,” and selecting concepts from current ecology textbooks that might arguably belong to a normative set. All ESA members were invited to participate in an online survey in October 2014 in which they rated 70, randomly selected concepts (out of a total set of 131) in terms of utility. Alternative to rating, respondents could mark the concept as unfamiliar. Respondents were also able list concepts that were important to them that were not encountered in the survey. Fifteen percent (1324) of the ESA membership participated in the survey. Of these, 89% were addressed in North America, 62% were male, 77% held Ph.D. degrees, 67% were involved in academia through employment or as students, and about one‐half of the total were divided between community and ecosystem ecology domains of interest. The 10 highest ranked concepts (in descending order) for utility were scales (small, local, regional, global, etc.), ecosystem, habitat, species, disturbance/perturbation, organism, population, community, competition, and species life history. The 10 lowest ranked concepts (in descending order) for utility were Lotka‐Volterra predator–prey/competition models, Allee effect, nutrient spiraling, character displacement, doubling time, climax, Hardy‐Weinberg equation, red queen hypothesis, chemoautotroph/chemoautotrophy, and mimicry. Respondents entered 2800 terms not encountered in the survey. After parsing for concepts missed due to the survey's random presentation process, for semantic redundancy and for terms deemed non‐concepts, 119 candidate concepts emerged. Many of these deserve consideration for inclusion in a normative set and introduction in textbooks. This research provides a well‐considered definition of “concept,” a basis for defining a normative set of concepts expected to be known to all ecologists, and a measure of familiarity but, more importantly, a measure of usage by contemporary ecologists who were members of ESA. These results help us to understand ourselves and our science, to better teach ecology, to guide the initiatives of the collective ecological community, and to further explore the extent and intellectual structure of the principal concepts by which ecologists pursue their work.